Thermal tolerance and sensitivity of amphibian larvae from Paleartic and Neotropical communities - Novo, Marco Jacinto Katzenberger Baptista (2009)
Tese de mestrado, Biologia (Biologia da Conservação), 2009, Universidade de Lisboa, Faculdade de Ciências